ANALISA LAPORAN KEUANGAN DAN INDIKATOR KEBANGKRUTAN PADA PT. MAYORA INDAH TBK - Siti Aisyah; Syamsul Bahri (Jurnal Inovasi Penelitian, 2021)
One way that the company can do so that the company survives, namely by analyzing the company's financial statements, which aims to find out the company's financial situation and development from year to year. The author conducted research on PT. Mayora Indah Tbk, a company engaged in the processed food industry. The purpose of this study is to compare the balances that are considered related, which can reflect the company's financial position and the company's performance. This comparison is better known as the ratio. In addition to the analysis of financial statements, an analysis of indicators of bankruptcy is also carried out on the company's financial statements. Which aims to be able to find out how the condition of a company, whether the company is experiencing financial difficulties and or the possibility of bankruptcy. The research method used in this research is a case study research method with data analysis techniques that use the financial ratio method to determine the performance and financial position of PT. Mayora Indah Tbk, and the bankruptcy method of Altman Models to determine the viability of PT. Mayora Indah Tbk. From the results of the analysis, it shows that the performance and financial position of PT. Mayora Indah Tbk in 2014 to 2018 can be said to be still quite good in the midst of unstable economic turmoil in the period concerned. Where seen from the liquidity ratio and debt management ratio, the company is able to pay off its obligations; for asset management ratios, the company is able to utilize its resources effectively and efficiently; for its profitability ratio, the company has decreased. For the analysis of bankruptcy indicators, the results obtained from 2014 to 2018, the company entered the gray area. Thus, the company is expected to be able to improve itself by knowing the existing weaknesses, and be able to immediately make improvements in order to obtain better results in the coming year.